Refractory cardiogenic shock in hypertrophic cardiomyopathy complicated by apical ballooning: A case report - Strycek, Matej; Polasek, Rostislav; Tomasov, Pavol; Karasek, Jiri (The Journal of international medical research, 2025)
Hypertrophic cardiomyopathy can be accompanied by dynamic obstruction in the left ventricular outflow tract and acute apical ballooning, which are among the very rare causes of cardiogenic shock. This condition requires a specific treatment approach that in many ways differs from the treatment of other causes of cardiogenic shock. We present a case and our treatment strategy (including extracorporeal life support) for refractory cardiogenic shock in a patient with previously undiagnosed hypertrophic cardiomyopathy.
Keywords: Cardiomyopathy, Hypertrophic; Humans; lidé středního věku; case report; Takotsubo Cardiomyopathy; mechanical circulatory support; Shock, Cardiogenic; Takotsubo syndrome; Female; hypertrofická kardiomyopatie; lidé; kardiogenní šok; takotsubo kardiomyopatie; Cardiogenic shock; left ventricular outflow tract obstruction; acute heart failure; extracorporeal membrane oxygenation; ženské pohlaví; Male; Middle Aged; hypertrophic cardiomyopathy; mužské pohlaví